Prática docente e a resolução de problemas matemáticos no contexto de mudança curricular do Estado de São Paulo: utopias e desafios - Buranello, Luciana Vanessa de Almeida [UNESP] (2014)
In the context of curricular reform started in 2008 by São Paulo Board of Education, the present thesis investigates the limits and possibilities offered to Math teachers, in order to re-structure their teaching practice when dealing with the Problems Resolutions. Questionnaires have been used to collect data, discussing the curricular reform, Math curriculum and Problems Reslution; classroom follow-up forms, descriptive accounts of contents recorded in audio and notes taken in class during researched teachers' presentations. The participants, linked to one of the 91 Teaching Councils in São Paulo State, have been organized in three groups: management team, math teachers, and two other teachers from the 9th grade Basic State School. Through an hermeneutical interpretation and phenomenological approach, it has been possible to verify that in the context of curricular configuration, and bearing in mind the idea of a curriculum as practice, problems resolutions is a methodological perspective that is hardly ever found in math classes, due to the influence of sub-systems, political-administrative and pedagogical, which frequently expose teachers to intense intellectual and pshychological effort. Dealing with complex issues such as teaching standardization, lack to concept from students, a curriculum structure based on the idea of a network, and the control of pedagogical practice, historically present at public educational policies, mainly during the process of curricular configuration, becomes an obstacle for the teaching of Problem Resolution to come true. In other words, from studies based on Hargreaves (2002), Sacristán (2000), Sternberg (2010), Pozo (1998), among others, we point out the controversial employment of problems resolutions in math classes, considering how little promising the scenery is for it to become a reality. Thus, problems resolution starts being seen as an additional mechanism in the control of pedagogical practice...